Electro-activation of sweet defatted whey: Impact on the induced Maillard reaction products and bioactive peptides. (15th April 2017) - Kareb, Ourdia; Gomaa, Ahmed; Champagne, Claude P.; Jean, Julie; Aïder, Mohammed
Highlights: Electro-activation modified whey composition and properties. Electro-activation generated active peptides in whey. Electro-activation suitable for integral whey valorization. Abstract: Electro-activation was used to add value to sweet defatted whey. This study aimed to investigate and to characterize the bioactive compounds formed under different electro-activation conditions by molecular and proteomic approaches. The effects of electric current intensity (400, 500 or 600 mA) and whey concentration (7, 14 or 21% (w/v)) as a function of the electro-activation time (0, 15, 30 or 45 min) were evaluated. The targeted dependent variables were the formation of Maillard reaction products (MRPs), protein hydrolysates and glycated compounds. It was shown that the MRPs derived from electro-activated whey at a concentration of 14% had the highest potential of biological activity. SDS–PAGE analyses indicated the formation of hydrolysates and glycated compounds with different molecular weight distributions. FTIR indicated the predominance of intermediate MRPs, such as the Schiff base compounds. LC–MS/MS and proteomics analysis showed the production of multi-functional bioactive peptides due to the hydrolysis of whey proteins.